Prevalence of feline coronavirus, feline leukemia virus, and feline immunodeficiency virus in client-owned cats in Croatia - Raukar, Jelena (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2021)
This study aimed to determine prevalences for anti-FCoV antibody, FeLV antigen, FeLV proviral DNA, and anti-FIV antibody among client-owned cats from the cities of Zagreb and Varaždin in Croatia. Subjects included 106 client-owned cats tested at the Faculty of Veterinary Medicine, Vienna, Austria. Blood samples were tested with IFA for anti-FCoV antibody and IFA FCoV antibody titeres, with ELISA for FeLV p27 antigen, with PCR for FeLV proviral DNA, and with RIM for anti-FIV antibody. Prevalence of FCoV and FeLV was 41.51% and 6.60%, respectively. A coinfection with FeLV/FCoV and FIV/FCoV prevalence was 7.55% and 5.66%. No cats were coinfected with FIV and FeLV. All three viruses were detected, confirming their presence in Croatia. The seroepidemiological findings demonstrate that both feline retroviruses and feline coronavirus are important feline pathogens in Croatia.